Molecular basis of PIP2-dependent regulation of the Ca2+-activated chloride channel TMEM16A - Son C. Le (Nature Portfolio, 2019)
The calcium-activated chloride channel (CaCC) TMEM16A plays crucial roles in regulating neuronal excitability and muscle contraction. Here authors show that phosphatidylinositol (4,5)-bisphosphate (PIP2) regulates TMEM16A channel activation and desensitization via binding to a putative binding site.